Transient analysis of printed lines using finite‐difference time‐domain method. (29th March 2012) - Ahmed, Shahid
SUMMARY Comprehensive studies of ultra‐wideband pulses and electromagnetic coupling on printed coupled lines have been performed using full‐wave 3D finite‐difference time‐domain analysis. Effects of unequal phase velocities of coupled modes, coupling between line traces, and the frequency dispersion on the waveform fidelity and crosstalk have been investigated in detail. To discriminate the contributions of different mechanisms into pulse evolution, single and coupled microstrip lines without (ϵr = 1) and with (ϵr > 1) dielectric substrates have been examined. To consistently compare the performance of the coupled lines with substrates of different permittivities and transients of different characteristic times, a generic metric similar to the electrical wavelength has been introduced. The features of pulse propagation on coupled lines with layered and pedestal substrates and on the irregular traces have been explored. Physical interpretations of the simulation results are discussed in the paper. Copyright © 2012 John Wiley & Sons, Ltd.